Interpreting non-linear drug diffusion data: Utilizing Korsmeyer-Peppas model to study drug release from liposomes - Wu, Iren Yeeling; Bala, Sonali; Škalko-Basnet, Nataša; di Cagno, Massimiliano Pio (European journal of pharmaceutical sciences, 2019)
The aim of this work was to clarify the dynamics behind the influence of ionic strength on the changes in drug release from large unilamellar vesicles (LUVs). For this purpose, we have investigated the transport of two different model drugs (caffeine and hydrocortisone) formulated into liposomes through different types of barriers with different retention properties (regenerated cellulose and the newly introduced biomimetic barrier, Permeapad®). Drug release from liposomes was studied utilizing the standard Franz diffusion cells. LUV dispersions were exposed to the isotonic, hypotonic and hypertonic environment (difference of 300 mOsm/kg between the initial LUVs and the environment) and experimental data treated with both linear and non-linear (Korsmeyer-Peppas) regression models. To alter the rigidity of the liposomal membranes, cholesterol was introduced in the liposomal barriers (up to 25% w/w). Korsmeyer-Peppas model was proven to be suited to analyse experimental data throughout the experimental time frame, providing important additive information in comparison to standard linear approximation. The obtained results are highly relevant as they improve the interpretation of drug release kinetics from LUVs under osmotic stress. Moreover, the findings can be utilized in the development of liposomal formulations intended for nose-to-brain targeted drug delivery. [Display omitted]